AGRICULTURAL SCIENCE AS A COMPONENT OF THE CURRICULUM OF SENIOR HIGH SCHOOL INTEGRATED SCIENCE IN GHANA. – ITS EFFECTS AND THE WAY FORWARD - Darko, Ransford Opoku; Yuan, Shouqi; Okyere, Davies; Ansah, Christina Offei; Liu, Junping (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The study sought to examine Agricultural Science as a component of the curriculum of Senior High School Integrated Science – its effects and the way forward within selected schools in the Greater Accra Region. The study adopted the descriptive survey research design. The research population was 150 students and 14 Integrated Science teachers. The disproportional, and census sampling techniqueswere used in selecting the participants for the study. Questionnaire made up of open and closeended questions were used to collect data. The findings of the study revealed the students’ knowledge level in Agriculture was low. Moreover, the teaching and learning of Integrated Science in the Senior High Schools was found to be bedeviled by challenges such as inadequate training for Integrated Science teachers, inadequate Integrated Science textbooks in the schools’ library, insufficient time allocation among others. Based on the findings of the study, it is recommended among others that the government, Parents Teachers Association (PTA) and other stakeholders should help in providing the needed resources and instruments needed that are needed for the effective teaching and learning of Agricultural Science and Integrated Science as a whole.